2022
DOI: 10.3390/molecules27227707
|View full text |Cite
|
Sign up to set email alerts
|

Camel Grass Phenolic Compounds: Targeting Inflammation and Neurologically Related Conditions

Abstract: Background: The use of plants for therapeutic purposes has been supported by growing scientific evidence. Methods: This work consisted of (i) characterizing the phenolic compounds present in both aqueous and hydroethanol (1:1, v/v) extracts of camel grass, by hyphenated liquid chromatographic techniques, (ii) evaluating their anti-inflammatory, antioxidant, and neuromodulation potential, through in vitro cell and cell-free models, and (iii) establishing a relationship between the chemical profiles of the extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The impacts observed are mainly ascribed to the antioxidative and anti-inflammatory characteristics of polyphenols, as reported by Lopes and collaborators [196]. In cases where there are changes to the BBB, they can even enhance its permeability [192].…”
Section: Neuroprotective Activitymentioning
confidence: 75%
“…The impacts observed are mainly ascribed to the antioxidative and anti-inflammatory characteristics of polyphenols, as reported by Lopes and collaborators [196]. In cases where there are changes to the BBB, they can even enhance its permeability [192].…”
Section: Neuroprotective Activitymentioning
confidence: 75%
“…It has been observed that, when consumed, phenolic compounds may function as natural inhibitors of enzymes involved in glucose metabolism, particularly α-glucosidase and α-amylase [7]. Additionally, several phenolic compounds can cross the blood-brain barrier (BBB) and have important biological effects in in vitro and in vivo models of neurodegenerative diseases, which are mainly associated with their antioxidant and anti-inflammatory capacity [8] and can even improve permeability when there are BBB alterations [9].…”
Section: Introductionmentioning
confidence: 99%